Rumen Fermentation, Blood Metabolites, and Performance of Sheep Fed Tropical Browse Plants - D A Astuti; A S Baba; I WT Wibawan (Media Peternakan, 2011)
The in vitro study was designed to evaluate total gas production, dry matter degradability (DMD), and VFA profile; while in vivo study was designed to evaluate nutrient intakes, blood metabolites, and performance of sheep fed native grass mixed with Calliandra calothyrrus (CC), Leucaena leucochepala (LL), Moringa oleifera (MO), Gliricidea sepium (GS), and Artocarpus heterophyllus (AH). The best three from the in vitro results were used to formulate diets in in vivo study. Sixteen male growing sheep (average BW 20 kg) were fed 100% native grass (NG) as control; 70% NG + 30% GS; 70% NG + 30% MO; and 70% NG + 30% AH. Nutrient consumptions, DMD, blood metabolites, and sheep performances were analyzed by using Completely Randomized Design. The in vitro results showed that the total gas production and DMD of CC and LL were the lowest (P<0.05) while the highest was found in GS, MO, and AH treatments (P<0.05). Meanwhile, the in vivo results showed that nutrient intakes (DM, CP, and CF) of GS and AH rations were the highest. The ADG, concentration of albumin, and globulin in all treatments were similar, while total serum protein, triglycerides, and glucose concentration in MO and AH rations were higher than others. Serum cholesterol concentration in MO ration was the lowest, meanwhile the concentration of IgG was the highest (P<0.05). Supplementation of 30% MO was the best choice for optimum rumen fermentation and  maintaining  health status of local sheep.